A CORPUS BASED ANALYSIS OF BE GOING TO AND BE ABOUT TO BY USING BRIGHAM YOUNG UNIVERSITY- BRITISH NATIONAL CORPUS (BYU-BNC) - Mirza Mirza; Yanuarius Yanu Dharmawan (Universitas Bandar Lampung, 2017)
The purpose of this study is to determine the difference between be going to and be about to using data from BYU-BNC corpus. In future tense, there are several kinds of modals. Among them are will, be going to and be about to. In general, most people use will and be gpoing to. However, they do not yet know that there is one kind of modal in the future tense that is be about to. In fact, the use of be going to and be about to is different. In this research, I use online dictionaries and corpus data. In this study, I used qualitative description and corpus data. An online dictionary is selected because the results in can be the recent results. Meanwhile, the selection of corpus as data collection because the corpus can provide an example of the data we seek in accordance with everyday life. From the first 100 lines in the corpus in each phrase will be selected with the same verb. Then, the data is translated to get the meaning of each sentence and determine the function of both phrases. The results of this study indicate that the use of be going to and be about to can be used to express about what will happen in the future. However, there are some functional differences between the two phrases. Be going to can be used to declare someone’s intention to do something. It can also be used to declare or expect what will happen in the future. Meanwhile, be about to is used to express about what is closed to happen. In the form of a negative sentence, not to be about to can be used to declare that we have no intention or unwillingness to do anything.